First record of Hodgson’s Bat Myotis formosus Hodgson, 1835 (Chiroptera: Vespertilionidae, Myotinae) from the Western Ghats, India - Chakravarty, Rohit; Dalvi, Shashank; Sankararaman, Vishnupriya; Girish, D. V. (Journal of the Bombay Natural History Society (JBNHS), 2014)
No Abstract.